ANALISIS TERHADAP PERILAKU ETIS AKUNTAN MASA DEPAN (Studi Empiris Pada Mahasiswa Akuntansi Universitas Sains Al Qur’an) - Nanang Agus Suyono (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2018)
This study aims to prove the influence of gender, religiuistas, learning achievement and intellectual capital to ethical behavior of accountants of the future. This study uses primary data in the form of questionnaires obtained from students majoring in accounting semester VII at UNSIQ. The population of this study is a student majoring in accounting at UNSIQ. Determination of sample by using puposive sampling. Based on the predetermined criteria, it was obtained as many as 113 students majoring in accounting semester VII. Hypothesis testing is done by using multiple regression analysis. The results of this study: Gender positively affects the ethical behavior of future accountants. Religiosity positively affects the ethical behavior of future accountants. Learning achievement negatively affects the ethical behavior of future accountants. Intellectual capital positively affects the ethical behavior of future accountants. Keywords: Gender, religiosity, learning achievement and intellectual capital